2020
DOI: 10.1016/j.psj.2019.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Yeast culture promotes the production of aged laying hens by improving intestinal digestive enzyme activities and the intestinal health status

Abstract: Yeast culture ( YC ) positively affects the performance of laying hens. The purpose of the present study was to explore the underlying mechanism for the YC-mediated performance improvement. Sixty 67-week-old Hy-Line Brown laying hens were randomly allocated into 2 experimental groups with 5 replicates of 6 birds each. One group was fed a control diet, whereas the other received the control diet supplemented with YC at 3.0 g/kg; treatment lasted for 8 wk. The results showed that dietary Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 45 publications
5
36
0
Order By: Relevance
“…Based on the observations of declined intestinal barrier function and compromised digestive physiology of aging laying hens, absorbed nutrients that involved in the formation of eggs might change, and it can be one of the major reasons for the poor egg quality of old layers ( Zhang et al., 2020 ). In agreement with a previous study ( Silversides and Scott, 2001 ), egg weight was observed to increase with age in the present experiment, and the higher weight ratio of yolk to white might contribute to this effect of aging on egg weight ( Ahn et al., 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the observations of declined intestinal barrier function and compromised digestive physiology of aging laying hens, absorbed nutrients that involved in the formation of eggs might change, and it can be one of the major reasons for the poor egg quality of old layers ( Zhang et al., 2020 ). In agreement with a previous study ( Silversides and Scott, 2001 ), egg weight was observed to increase with age in the present experiment, and the higher weight ratio of yolk to white might contribute to this effect of aging on egg weight ( Ahn et al., 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…All birds were allowed access to the mash diets and water ad libitum for the 12-week exposure period. Feed intake, egg weight, and bird mortalities were recorded daily [ 49 ]. The feed/egg ratio, egg production rate, and interior egg quality were calculated every four weeks.…”
Section: Methodsmentioning
confidence: 99%
“…The feed/egg ratio, egg production rate, and interior egg quality were calculated every four weeks. Eggshell quality and egg mycotoxin concentrations were measured on the last day of the twelfth week [ 49 ]. At the end of the feeding trial, 10 birds from each group were slaughtered to collect blood samples, duodenum, jejunum, and ileum for serological and histological examination, as previously described [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several experiments have suggested that YC has a positive effect on layers and broilers. For example, Zhang J.C. et al (2020) reported that YC addition at 3.0 g/kg of feed improves the performance of aged layers by upregulating intestinal digestive enzyme activity and intestinal health-related gene expression. Another study in broilers showed that dietary YC supplementation at 0.1 g/kg increases daily weight gain and reduces Campylobacter in the cecum ( Froebel et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, studies have also reported that this immunity induced by YC is passed on to offspring and reduces symptoms of coccidiosis infection ( Lu et al, 2019 ; Sun and Kim, 2019 ). In addition, some previous studies have shown that YC administration positively affects poultry laying performance and intestinal health ( Zhang J.C. et al, 2020 ). We suspect that this is because of improvements within the intestinal microbiota community, which then increase the proportion of beneficial microorganisms and inhibit the reproduction of harmful microorganisms.…”
Section: Introductionmentioning
confidence: 99%